Addition of a probiotic containing microenscapsulated Lactobacillus plantarum to chicken feed - Jurado-Gámez, Henry Armando; Zambrano-Mora, Edward Johnny; Pazos-Moncayo, Alvaro (Universidad y Salud, 2021)
Introduction: Introduction: Usage of growth-promoting antibiotics in poultry production is limited due to the increase in bacterial resistance. An alternative to assess microencapsulated probiotics and their effect on gut health is presented in this study. Objective: To determine the effect of microencapsulated Lactobacillus plantarum on intestinal and immunological parameters in broilers. Materials and methods: 240 Ross-308-AP chickens (one day old) were fed with or without the addition of a probiotic, under the following model: without probiotic (T0); with commercial probiotic (T1); with probiotic containing either microencapsulated (T2) or non-microencapsulated (T3) L. plantarum. ATCC-8014 was microencapsulated by spray drying, assessing its viability in (%). Alcian blue, scanning microscopy, and immunohistochemistry were used to evaluate intestinal, morpho-histopathological, and immunological parameters. Microbial abundance was quantified by UFC/ml. Results: Microencapsulation of L. plantarum induced an 88.1% in vivo viability. T2 treatment improved both immunological parameters and the intestinal population of beneficial bacteria (Lactobacillus) (9.13x105 UFC/ml), which was significantly higher than that found in T1 (8.91x105), T3 (8.23x105), and control T0 (9.18x104), (p<0.05). Conclusion: Adding microencapsulated L. plantarum to chicken feed improves immunological parameters and increases the population of beneficial bacteria in the intestinal microbiota.